Selective posterior rhizotomy for the treatment of pure hereditary spastic paraplegia⁃ associated lower limb spasticity - TANG Nan; SHEN Yin; WANG Lei; ZHENG Jiang‐lin; HUANG Ning; ZHOU Ying‐chun (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective To evaluate the efficacy and safety of selective posterior rhizotomy (SPR) for the treatment of pure hereditary spastic paraplegia (PHSP) ⁃ associated lower limb spasticity. Methods Nine patients with PHSP were admitted to Union Hospital, Tongji Medical College, Huazhong University of Science and Technology from January 2021 to February 2023. The Ashworth Scale (AS) score of hip adductors, quadriceps femoris, triceps surae and hamstring, femoral angle, popliteal fossa angle and dorsiflexion angle of foot, and Gross Motor Function Classification System (GMFCS) score before and after surgery were analyzed. Postoperative complications were recorded. Results All 9 patients completed SPR. No serious complication was observed. The AS score before and after surgery were significantly different of hip adductors (F = 43.568, P = 0.000), quadriceps femoris (F = 43.000, P = 0.000), triceps surae (F = 59.200, P = 0.000) and hamstring (F = 116.138, P = 0.000). The AS score of hip adductors (P = 0.000, 0.000), quadriceps femoris (P = 0.000, 0.000), triceps surae (P = 0.000, 0.000) and hamstring (P = 0.000, 0.000) 1 d and 12 months after surgery were significantly decreased comparing with those before surgery. The femoral angle (t = ⁃ 17.812, P = 0.000) and popliteal angle (t = ⁃ 12.791, P = 0.000) 5 d after the surgery were significantly increased comparing with those before surgery, while the dorsiflexion angle of foot 5 d after surgery was significantly decreased comparing with that before surgery (t = 14.050, P = 0.000). The GMFCS score before and 12 months after surgery were no significantly different (t = 1.000, P = 0.347). Conclusions SPR has good efficacy and safety for the treatment of PHSP⁃associated lower limb spasticity.